(untitled) (Journal of Philosophy Culture and Political Science, 2020)
Pythagoras and his followers wrote works related to abstract numbers in Greek philosophy and they tried to create a philosophy of infinite being on the basis of mathematics. They believed that numbers were created by God and characterized numbers as religious phenomenon and thought that the whole world consists of these numbers and their scope. Pythagoras was the author of the word: “Ruler of the world is numbers. Numbers rule the world”. In the views of Pythagoras, “without numbers, nothing can be understood or learned. Therefore, numbers carry the root of all developments, and there is nothing wiser than that. That means, these numbers tend to be God. In ancient civilizations, Judaism, Christianity and Islamic philosophy – the philosophy of this Pythagoras was based on an interest in the ontological characteristics of numbers. Positive integers, called natural numbers, are one of the most amazing discoveries of the human brain. The history of mankind amazes with the mystical significance of the numbers of Pythagoras even today, which has not lost its relevance. This article discusses the relation of numbers from 1 to 10 (including 10) and its ontological and metaphysical structure that has been studied since the time of Pythagoras with the infinite being. Key words: concept of numbers, Pythagoras, metaphysics of numbers, symbol, infinite being.